Foreign Policy Of India Under BJP Government (Journal of Namibian Studies : History Politics Culture, 2023)
India has risen as a major player in the geo-politics at an international level. Part of this rise can be attributed to its dynamic and adaptive Foreign Policy. With changes in regimes, India's emphasis on its Foreign Policy has wavered over the years in response to shifting global geopolitical dynamics. Some things have remained constant; some things, however, have brought changes in the position of the country in the global world. The dynamics of India's foreign policy is something that affect us as citizens and residents of India in some form or the other. India's Foreign Policy, however, has  evolved over the years in a changing global landscape, and facing the challenges in a contemporary world.